Comportamento de busca e uso da informação de universitários indígenas do campus IV – UFPB - Lima, Kamilla Rebeca Souto Queiroz de (2019)
In recent years, public education policies in higher education have contributed to the inclusion of indigenous people in universities. However, indigenous university students, as information users, face difficulties during graduation that can interfere in their academic development. The access and use of information are primordial for intellectual and social inclusion of the less favored classes, in which the intervention of Information Science seeks to mediate with the indigenous university students in overcoming their informational gaps. In order to understand how the information search behavior of the indigenous university students is configured, the research project aims to analyze the behavior of search and use of the information by the indigenous university students of Campus IV of the UFPB in the light of the Ellis Model, Cox and Hall (1993) expanded with the contributions of Crespo (2005), and Tabosa and Pinto (2015). It is an exploratory and descriptive research and quantitativequalitative approach. The study contemplates two phases: the bibliographical research, to compose the theoretical reference and a field research, with the application of a survey composed by open and closed questions. The research subjects are the indigenous university students of the CCAE-Campus IV of the UFPB, with active links with the institution and enrolled in the 2018.1term. The data analysis of the research was carried out based on the Bardin Content Analysis, with presentation of results through statistical inferences and graphs and tables representation. The results of the research point out that the profile of IUs are, mostly between 21 and 30years old, female and low family income (up to two minimum wages) They are village Indians, take courses in education field, did not attend a differentiated school in regular education and entered the university through racial quotas. It can be verified that the informational behavior of indigenous university students contemplates intense use of books and the Internet as channels and sources of information. Regarding search behavior, UI prefer to start their searches in books and the internet. Chain activity is done by most users surveyed, but browsing, monitoring, and checking activities are not widely practiced. The differentiating action is carried out mostly by the indication of teachers and colleagues, relevance of the subject and credibility of the authors. Finishing is achieved by satisfaction and personalization by adding page to bookmarks and highlighting items of interest. The extraction takes place mainly in websites and books. Sharing occurs mostly by passing information to friends and relatives and posting on social networks. Conclusion is that UFPB campus IV UIs use the Internet extensively and its information search and use behavior is in accordance with a current trend of intensive use of electronic information sources.